Forest, fire & monsoon: investigating the long-term threshold dynamics of south-east Asia's seasonally dry tropical forests. (15th June 2020) - Hamilton, Rebecca; Penny, Dan; Hall, Tegan L.
Abstract: Tropical forests are the most biodiverse terrestrial ecosystems on earth, yet are particularly susceptible to future climatic and human-induced change. Identifying tipping points at which tropical ecosystems will reorganise is therefore an important research goal. Limited research within the seasonally dry tropical forests of south-east Asia means that much uncertainty exists around the resilience of these systems to future global change. This is a critical research gap because these forests should – given their physiognomic attributes, current bioclimatic envelope and the range of stressors – be very sensitive to a stable-state shift to savanna. Here we adopt a palaeoecological approach to examine the interaction between key drivers of change (decreased precipitation and heightened fire activity) and forest response over ∼4700 years though interrogation of sediment-based proxies from volcanic crater lakes within north-east Cambodia – in the core range of southeast Asia's tropical dry forests. Our results suggest that rapidly regenerating, secondary forest taxa are important for maintaining a forested state when the landscape is subject to moderate fire and climatic disturbance. However, when these stressors are amplified, recovery and resistance traits associated with key deciduous dipterocarp forest taxa appear critical for forest stability. Notably, shifts from more closed, seasonal evergreen forest formations to more open secondary/deciduous dipterocarp formations appear reversible when the stressors are removed, suggesting that these transitions are not analogous with the difficult-to-reverse, forest-to-savanna stable state shifts that occur elsewhere in Neotropical and Afrotropical settings. Our results indicate that the resilience of south-east Asian forests to climatic forcing appears contingent on the maintenance of secondary forest, deciduous forest, and seasonal evergreen dry forest mosaics across the ecoregion. This has implications for the conservation and wise-use of mainland south-east Asia's lowland dry forests. Highlights: We explore the response of Asian seasonal forests to fire and drought over 4.7ka. Landscape mosaics support forest recovery and resistance in response to disturbance. Maintaining traditional swidden techniques appears important for forest conservation. SE Asian forest resilience to fire and drought contradicts global biome theory. Resilience is contingent on evolutionary history and landscape heterogeneity.